2012
DOI: 10.1016/j.cpr.2012.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Face-to-face versus computer-delivered alcohol interventions for college drinkers: A meta-analytic review, 1998 to 2010

Abstract: Alcohol misuse occurs commonly on college campuses, necessitating prevention programs to help college drinkers reduce consumption and minimize harmful consequences. Computer-delivered interventions (CDIs) have been widely used due to their low cost and ease of dissemination but whether CDIs are efficacious and whether they produce benefits equivalent to face-to-face interventions (FTFIs) remain unclear. Therefore, we identified controlled trials of both CDIs and FTFIs and used meta-analysis (a) to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
285
4
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(304 citation statements)
references
References 88 publications
12
285
4
3
Order By: Relevance
“…The search strategies are shown in Appendix Table 2 (available at www.annals.org). We reviewed bibliographies of included trials and applicable systematic reviews for missed publications (14)(15)(21)(22)(23)(24)(25). To assess for publication bias, we searched ClinicalTrials.gov for trials that met our eligibility criteria (26) and found 2 trials that were completed at least 1 year before our literature search but were unpublished.…”
Section: Data Sources and Searchesmentioning
confidence: 99%
“…The search strategies are shown in Appendix Table 2 (available at www.annals.org). We reviewed bibliographies of included trials and applicable systematic reviews for missed publications (14)(15)(21)(22)(23)(24)(25). To assess for publication bias, we searched ClinicalTrials.gov for trials that met our eligibility criteria (26) and found 2 trials that were completed at least 1 year before our literature search but were unpublished.…”
Section: Data Sources and Searchesmentioning
confidence: 99%
“…Las IB fueron realizadas en todos los casos a mujeres gestantes ya sea cara-cara o vía web, lo que coincide con el estado de las investigaciones actuales en IB, donde las intervenciones vía web han cobrado especial protagonismo en los últimos diez años (33,34) por ser un medio de intervención que en algunos contextos ha demostrado ser costo-efectivo y alcanzar a una gran cantidad de personas (35,36). Sin embargo debe tenerse en consideración que en el contexto latinoamericano las intervenciones vía web tienen una menor tasa de respuesta en comparación con estudios de lápiz y papel, probablemente por características socioculturales como mayor desconfianza en el uso de los medios electrónicos y preferencias de contactos interpersonales más cercanos (37).…”
Section: Discussionunclassified
“…They are as effective as alternative interventions offered face-to-face by a therapist when compared with controls but, in direct comparisons, face-to-face interventions have been shown to be more effective for both quantity and problem measures and in terms of long-term effects [46,47]. …”
Section: Introductionmentioning
confidence: 99%
“…Automated stand-alone computer-delivered brief alcohol interventions, regardless of delivery mode, offer small but meaningful effects in a wide range of alcohol-related measures [41,42,43,44,45,46,47]. They are as effective as alternative interventions offered face-to-face by a therapist when compared with controls but, in direct comparisons, face-to-face interventions have been shown to be more effective for both quantity and problem measures and in terms of long-term effects [46,47].…”
Section: Introductionmentioning
confidence: 99%